ESG Performance and Dividend Policy: Role of Board International Experience - Aulia, Sandra; Hambali, Ahmad; Johari, Razana Juhaida; Lim, Ivy B.; Cura, Christopher T. (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
This study aims to examine the impact of Environmental, Social, and Governance (ESG) performance on corporate dividend policy, as well as the moderating role of the board of directors' international experience in this relationship. With the growing global focus on sustainability, ESG has become a crucial factor in corporate strategy, not only enhancing reputation and competitiveness but also representing social responsibility. Previous studies have shown mixed results regarding the influence of ESG performance on corporate financial outcomes, particularly on dividend policy. This study focuses on companies in the ASEAN region, where corporate governance and investor protection tend to be weaker compared to developed countries. Analysis of data from ASEAN companies indicates that higher ESG performance is associated with more stable dividend policies. Additionally, the international experience of board members is found to positively impact dividend policy directly but does not strengthen the relationship between ESG performance and dividend policy. These findings contribute to a deeper understanding of the role of ESG and board characteristics in dividend policy, providing valuable insights for stakeholders in evaluating corporate sustainability practices.